2008
DOI: 10.1016/j.beproc.2008.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Matching-to-sample by pigeons: The dissociation of comparison choice frequency from the probability of reinforcement

Abstract: It has been proposed that comparison choice in matching-to-sample should depend on two factors, the relative probability of reinforcement associated with each of the comparison stimuli and the conditional probability of each comparison stimulus being correct given presentation of one of the samples. DiGian and Zentall (in press) have shown that sample frequency together with the probability of choosing each of the comparison stimuli in training can influence comparison choice when delays are introduced, when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
(15 reference statements)
1
10
0
Order By: Relevance
“…11). Instead of considering the probability of each sample given the pair of comparison stimuli presented, it appears that they considered the overall probability that it was the red sample, in spite of the fact that half of those presentations were not relevant to the two comparisons presented on that trial (see also, DiGian and Zentall, 2007;Zentall et al, 2008). Thus, it appears that animals too are susceptible to base-rate neglect and that basic behavioral processes are involved (see also Goodie and Fantino, 1996).…”
Section: Base-rate Neglectmentioning
confidence: 92%
See 3 more Smart Citations
“…11). Instead of considering the probability of each sample given the pair of comparison stimuli presented, it appears that they considered the overall probability that it was the red sample, in spite of the fact that half of those presentations were not relevant to the two comparisons presented on that trial (see also, DiGian and Zentall, 2007;Zentall et al, 2008). Thus, it appears that animals too are susceptible to base-rate neglect and that basic behavioral processes are involved (see also Goodie and Fantino, 1996).…”
Section: Base-rate Neglectmentioning
confidence: 92%
“…If so, Zentall et al (2008) have shown that pigeons tend to judge intervals as shorter when they are pecking than when they are not pecking. However, Santi et al (2010) tested this hypothesis by requiring that pigeons refrain from pecking during both the filled and unfilled intervals and it did not eliminate the judgments that the filled intervals were shorter than the unfilled intervals.…”
Section: Temporal Discriminationsmentioning
confidence: 96%
See 2 more Smart Citations
“…By doing so, they neglect the base rate with which choice of the comparison colors is reinforced. Interestingly, when pigeons are given the same task, they show better sensitivity to the base rates and get more correct than humans do (Fantino, Kanevsky, & Charlton, 2005); however, if pigeons are given extensive training on matching to sample with 100% reinforcement for matching and then are transferred to the task in which choice of one of the comparisons is reinforced most of the time, they, too, show evidence of base-rate neglect (see also DiGian & Zentall, 2007;Zentall & Clement, 2002;Zentall, Singer, & Miller, 2008). Thus, extensive experience with a task in which a stimulus (in this case, the sample) provides a highly reliable cue for correct comparison choice biases, pigeons tend to neglect the fact that the stimulus is no longer a reliable cue, resulting in suboptimal choice by the pigeons.…”
Section: Resultsmentioning
confidence: 99%